Bio-distribution and toxicity assessment of intravenously injected anti-HER2 antibody conjugated CdSe/ZnS quantum dots in Wistar rats - Dhermendra K Tiwari (Dove Medical Press, 2011)
Dhermendra K Tiwari1, Takashi Jin2, Jitendra Behari11School of Environmental Sciences, Jawaharlal Nehru University, New Delhi, India; 2WPI-Immunology Frontier Research Center, Osaka University, Osaka, JapanAbstract: Anti-HER2 antibody conjugated with quantum dots (anti-HER2ab-QDs) is a very recent fluorescent nanoprobe for HER2+ve breast cancer imaging. In this study we investigated in-vivo toxicity of anti-HER2ab conjugated CdSe/ZnS QDs in Wistar rats. For toxicity evaluation of injected QDs sample, body weight, organ coefficient, complete blood count (CBC), biochemistry panel assay (AST, ALT, ALP, and GGTP), comet assay, reactive oxygen species, histology, and apoptosis were determined. Wistar rat (8–10 weeks old) were randomly divided into 4 treatment groups (n = 6). CBC and biochemistry panel assay showed nonsignificant changes in the anti-HER2ab-QDs treated group but these changes were significant (P < 0.05) in QDs treated group. No tissue damage, inflammation, lesions, and QDs deposition were found in histology and TEM images of the anti-HER2ab-QDs treated group. Apoptosis in liver and kidney was not found in the anti-HER2ab-QDs treated group. Animals treated with nonconjugated QDs showed comet formation and apoptosis. Cadmium deposition was confirmed in the QDs treated group compared with the anti-HER2ab-QDs treated group. The QDs concentration (500 nM) used for this study is suitable for in-vivo imaging. The combine data of this study support the biocompatibility of anti-HER2ab-QDs for breast cancer imaging, suggesting that the antibody coating assists in controlling any possible adverse effect of quantum dots.Keywords: cancer bioimaging, HER2, anti-HER2 antibody, quantum dots, comet assay